PRIMARY PERITONITIS WITH POCKETED ABSCESS INTRAPERITONEAL CAUSED BY UMBILICAL CATHETER INFECTION IN 22 DAYS OLD BABY - -, Ariputra; Kardana, I Made; Darmajaya, Made (Medicina, 2014)
Primary peritonitis defined  as  a microbial  infection  of  the peritoneum  and peritoneal  fluid  in  theabsence of a gastrointestinal or visceral perforation. The source of infection is extra abdominal andmay arise  from  lymphatics  or blood  stream. One  of  the  infection  source  can be  extension  from anomphalitis  or  infected  umbilicus. Omphalitis  can  occur  due  to  complication  of Umbilical VeinCatheterization  (UVC). UVC  are used  to  provide  access  for  resuscitation,  frequent monitoring  ofblood, administration of fluids, blood and parenteral nutrition. We report a case of primary peritonitiswith  pocketed  intraperitoneal  abscess  caused  by umbilical  infection  in  22  days  old  baby. Patientpresent a clinical sign of peritonitis and severe omphalitis with history of using umbilical catheter. X-ray found a free fluid impression in the abdominal cavity. Patient undergo a laparotomy and pocketedintraperitoneal  abscess was  found  around  ligamentum  teres hepatis  area,  suspected  of  infectiouscomplications arising out from the use of umbilical catheter.  [MEDICINA 2014;45:193-198].